Removal of H2S to produce hydrogen in the presence of CO on a transition metal-doped ZSM-12 catalyst: a DFT mechanistic study. Issue 35 (27th August 2020) - Mudchimo, Tanabat; Kamchompoo, Suparada; Injongkol, Yuwanda; Rattanawan, Rattanawalee; Kungwan, Nawee; Jungsuttiwong, Siriporn
Abstract : The Cu–ZSM-12 catalyst is the most promising catalyst for H2 S removal together with producing hydrogen gas (a potentially useful fuel), with kinetically and thermodynamically favorable at ambient condition. Abstract : Hydrogen sulfide (H2 S) leads to corrosion in transport lines and poisoning of many catalysts. Meanwhile, H2 S is an inexhaustible potential source of hydrogen, which is a very valuable chemical reagent and an environmentally friendly energy product. Therefore, removal of H2 S and producing hydrogen gas using potential catalysts has been intensively studied, according to the equation: H2 S(g) + CO(g) → COS(g) + H2 (g). In this study, hydrogen sulfide (H2 S) decomposition in the presence of CO over transition metal-doped ZSM-12 clusters (TM-ZSM-12) has been investigated based on DFT calculations at the B3LYP-D3/6-31G(d, p) level. The calculation results reveal that the proposed reaction mechanism is controlled by 4 key steps, (i) hydrogen dissociation ( E a1 = +0.04 eV for the 1st hydrogen and E a2 = +0.22 eV for the 2nd hydrogen), (ii) COS desorption (the rate-determining step of this H2 S removal process, E des = +1.18 eV), (iii) hydrogen diffusion to the transition metal with an energy barrier ( E a3 ) of +0.62 eV, and (iv) the H2 formation step ( E a4 = +0.94 eV). Our results indicate that in the presence of CO, the Cu–ZSM-12 cluster has a potential application as a highly active catalyst for H2 S removal together with hydrogen production.